Exploring prevalent injuries among tennis players and optimal rehabilitation approaches: A systematic review protocol - Rodríguez-González, E. M.; Amor-Salamanca, M. S.; Rosselló, D.; Lluc-Bauza, M. de; Hermosilla-Perona, F.; Martín-Castellanos, A.; Herrera-Peco (PLOS ONE, 2024)
Introduction Tennis is a globally popular sport known for its numerous health benefits. However, it also underscores the physical demands and potential injuries associated with high-performance play. This review emphasizes the role of kinetic chains in executing powerful movements and discusses common injuries, particularly in the upper limbs due to the sport`s overhead nature. It highlights the importance of effective rehabilitation methods for swift recovery and long-term performance enhancement in high-performance tennis players.